2014
DOI: 10.1021/am505616x
|View full text |Cite
|
Sign up to set email alerts
|

Compact Bis-Adduct Fullerenes and Additive-Assisted Morphological Optimization for Efficient Organic Photovoltaics

Abstract: Bis-adduct fullerenes surrounded by two insulating addends sterically attenuate intermolecular interaction and cause inferior electron transportation. In this research, we have designed and synthesized a new class of bis-adduct fullerene materials, methylphenylmethano-C60 bis-adduct (MPC60BA), methylthienylmethano-C60 bis-adduct (MTC60BA), methylphenylmethano-C70 bis-adduct (MPC70BA), and methylthienylmethano-C70 bis-adduct (MTC70BA), functionalized with two compact phenylmethylmethano and thienylmethylmethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
(77 reference statements)
0
7
0
1
Order By: Relevance
“…Various approaches have been attempted to improve the blend morphology of the interconnected network of polymer donors and acceptors, such as adjusting the polymer molecular weight, D/A blending ratios, ,, thermal annealing, and solvent additive processing. Among these processing methods, solvent additive processing is considered as an effective and simple way to control the nanoscale structure of phase separation and polymer ordering in D/A blend systems. Neher et al demonstrated that 1-chloronaphthalene (CN) (1:1 p -xylene:CN) can suppress the preaggregation of the acceptor polymer, poly­[[ N , N ′-bis­(2-octyldodecyl)­napthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl]- alt -5,5′-(2,2′-bithiophene)] (P­(NDI2OD-T2)) in a poly­(3-hexylthiophene-2,5-diyl) (P3HT)/P­(NDI2OD-T2) blend film and showed that this phenomenon exhibited a large increase in J SC . Hou et al also reported an increased FF in a blend system consisting of benzo­[1,2- b :4,5- b ′]­dithiophene (BDT)–thiophene donor polymer (PBDTBDD-T) and BDT–naphthalene diimide (NDI) acceptor polymer (PBDTNDI-T) after processing chlorobenzene (CB) with 3 vol % CN and showed that this process induced high domain purity and improved the molecular ordering of the blend film.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been attempted to improve the blend morphology of the interconnected network of polymer donors and acceptors, such as adjusting the polymer molecular weight, D/A blending ratios, ,, thermal annealing, and solvent additive processing. Among these processing methods, solvent additive processing is considered as an effective and simple way to control the nanoscale structure of phase separation and polymer ordering in D/A blend systems. Neher et al demonstrated that 1-chloronaphthalene (CN) (1:1 p -xylene:CN) can suppress the preaggregation of the acceptor polymer, poly­[[ N , N ′-bis­(2-octyldodecyl)­napthalene-1,4,5,8-bis­(dicarboximide)-2,6-diyl]- alt -5,5′-(2,2′-bithiophene)] (P­(NDI2OD-T2)) in a poly­(3-hexylthiophene-2,5-diyl) (P3HT)/P­(NDI2OD-T2) blend film and showed that this phenomenon exhibited a large increase in J SC . Hou et al also reported an increased FF in a blend system consisting of benzo­[1,2- b :4,5- b ′]­dithiophene (BDT)–thiophene donor polymer (PBDTBDD-T) and BDT–naphthalene diimide (NDI) acceptor polymer (PBDTNDI-T) after processing chlorobenzene (CB) with 3 vol % CN and showed that this process induced high domain purity and improved the molecular ordering of the blend film.…”
Section: Introductionmentioning
confidence: 99%
“…6 It is notable that biscycloadducts work well only in combination with crystalline polymers such as P3HT and PBDTBDD. [3][4][5][6][7][8][9][10][11][12][13] The crystallization of the polymer during film formation also induces ordering of the fullerene phase. Furthermore, different isomers of biscycloadducts have rather different LUMO energies which induce energetic disorder in the material represented by a complex isomer mixture.…”
Section: Introductionmentioning
confidence: 99%
“…Identification, chromatographic separation, and purification of such isomers are very hard, nontrivial, and expensive tasks. Therefore, in the first works, fullerene bis- and trisadducts were introduced into photovoltaic devices as mixtures of regioisomers. , Later, it has been recognized that using the purified regioisomers substantially enhances key output parameters of OSCs. This has been first demonstrated with the solar cells based on the substituted bis­(dihyrdonaphtyl)­C 60 adducts in the foremost work .…”
Section: Introductionmentioning
confidence: 99%